Autonomous participation. An activist ethnography in Maranya Youth Club. Issue 2 (2nd April 2020) - Aguirre, Arecia; Moliner, Lidón; Traver, Joan A.
ABSTRACT: In this article there is a discussion about the results of an activist Ethnography carried out in Benicasim (Spain). The study is focused on the culture of youth participation in leisure spaces that contribute significantly to the education of young people as critical citizens. During 3 years of fieldwork as an activist in the Youth Club (YC) we carried out an investigation based on biographical, narrative, participatory and observational tools. Particularly, we try to understand which elements can turn a participatory structure into a tool for a model of participatory progression and offer the possibility of creating personalised participatory trajectories. Our results suggest that structuring participation in a youth club can be beneficial if we care for aspects like commitment, responsibility, availability, leadership and the sense of membership. Adapting these elements to the characteristics of each youth will boost participation to more autonomous levels, thus enabling an empowering and autonomous learning process.